Formulation design preparation and in vitro characterization of nebivolol transdermal patches - Nayak, Bhabani Shankar; Ellaiah, P; Pattanayak, Dharmajit; Das, Saumya (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of the present investigation is to develop and evaluate transdermal patches of nebivolol.The transdermal patches of nebivolol were prepared by solvent evaporation technique. Twelve formulations of nebivolol patches were prepared that composed of ethyl cellulose (EC) with hydroxyl propyl methyl cellulose (HPMC) and ethyl cellulose with polyvinyl pyrrolidine (PVP) in different ratios of 1:2, 1:4, 1:6, 2:1, 4:1, and 6:1 w/w, as film former. Polyvinyl alcohol (4% w/v) was used to prepare the backing membrane. All formulations contained Tween 80 (4% v/w) as penetration enhancer and propylene glycol (40% v/w) as plasticizer in dimethyl formamide as solvent system. The prepared transdermal patches of nebivolol were evaluated for thickness, mass variation, drug content, moisture content, moisture vapor transmission, folding endurance, tensile strength, ex vivo drug permeation study, drug release kinetics, scanning electron microscopy, primary skin irritancy study, and stability study. The physicochemical interactions between nebivolol and different polymers were studied by Fourier Transform Infrared (FTIR). The maximum drug release in 24 h was 95.185% (T2, HPMC:EC is 1:4), which is significant (P < 0.05). Furthermore, the formulation T2 showed maximum skin permeation (13.93 mg/cm2/h) in comparison with other formulations. The mechanical properties and tensile strength revealed that the formulations were found to be strong enough but not brittle. FTIR studies did not show any evidence of interaction between the drug and the polymers. Nebivolol matrix-type transdermal therapeutic systems could be prepared with the required flux having suitable mechanical properties.